Assessment of the environmental status in Hellenic coastal waters (Eastern Mediterranean): from the Water Framework Directive to the Marine Strategy Water Framework Directive. - N. SIMBOURA; M. TSAPAKIS; A. PAVLIDOU; G. ASSIMAKOPOULOU; K. PAGOU; H. KONTOYANNIS; C. ZERI; E. KRASAKOPOULOU; E. ROUSSELAKI; N. KATSIARAS; S. DILIBERTO; M. NALETAKI; et al. (Mediterranean Marine Science, 2014)
A methodology is presented to assess the environmental status sensu the Marine Strategy Water Framework Directive (MSFD) based on data obtained from the monitoring of water quality in the Hellenic coastal waters within the Water Framework Directive (WFD). An adapted decision tree used for integrating the results of the WFD in the Basque country was applied. Modifications lie to the evaluation of the physicochemical status based on a eutrophication index developed for Eastern Mediterranean waters. Results on hydromorphological, physicochemical and biological elements are presented. The chemical status was evaluated based on measurements of heavy metals in water. The evaluation of the biological quality was based on the use of metrics developed for phytoplankton biomass, benthic macroinvertebrates and macroalgae updated to accommodate MSFD needs. Results on the integrative status of the water bodies were validated by correlating classification results with a pressure index and environmental indicators in water column and sediment. Following this decision tree the majority of stations expected to be at risk of achieving the good status were found in moderate status. Benthos was found to be the element with the closest agreement with the integrated final status having an increased weighting in the decision tree. The quality of benthos and in some limited cases the eutrophication index determined largely the final status. The highest disagreement with the integrative classification was produced by macroalgae. All indicators used correlated with water and sediment parameters but benthos correlated better with sediment factors while phytoplankton and eutrophication index with water column parameters.

Assessing the ecological status of Mediterranean coastal lagoons using macroinvertebrates. Comparison of the most commonly used methods - S. REIZOPOULOU; N. SIMBOURA; K. SIGALA; E. BARBONE; F. ALEFFI; G. KAISAKIS; I. ROSATI; A. BASSET; A. NICOLAIDOU (Mediterranean Marine Science, 2014)
Benthic communities were studied twice (autumn and spring) in three Mediterranean coastal lagoons located in Greece (Logarou) and Italy (Cesine and Grado-Marano). The species composition and distribution, the community diversity, the species richness, the dominant taxa and their ecological identity, the benthic trophic and biomass size structure were investigated in these lagoons and the the results were correlated with environmental variables.The overall similarity based on species composition and abundance among lagoons was low due to differences in dominant environmental factors, whereas variations of community diversity and species richness were mainly related to the degree of marine influence, reflecting the natural structure. The benthic classification indices AMBI, M-AMBI, BENTIX, BO2A, ISD and ISS were applied to assess the ecological status of the lagoons studied. Results showed that the biotic indices AMBI, M-AMBI, BENTIX, and BO2A are not adequately efficient due to the natural dominance of tolerant and opportunistic species and the correlation of species diversity to natural stress. ISD and ISS on the other hand, based on size distribution frequencies and on size spectra sensitivity respectively, had a good discrimination power between impacted and unimpacted sites. Results indicate that alternatively to the species sensitivity, other traits of the communities as the biomass or size structure could be more robust, sensitive and effective in assessing the ecological quality in lagoons.

Benthic community indicators over a long period of monitoring (2000–2012) of the Saronikos Gulf, Greece, Eastern Mediterranean - N. Simboura; A. Zenetos; M. A. Pancucci-Papadopoulou (Environmental Monitoring and Assessment, 2014)

First record of Dipolydora blakei (Annelida: Spionidae) from Europe: Greece, Mediterranean Sea - V. I. RADASHEVSKY; N. SIMBOURA (Mediterranean Marine Science, 2013)
The spionid polychaete Dipolydora blakei is identified from benthic samples collected in the Aegean Sea off Chalkis and the Ionian Sea off Kalamitsi, both on the coast of Greece. Adults of D. blakei are characterized by having the falcate spines of chaetiger 5 with a large lateral tooth and bristles on the convex side of a long and pointed main fang, awl-like spines in posterior notopodia, branchiae beginning from chaetiger 7 and a pygidium with two lateral lobes. This is the first report of the species from the Mediterranean Sea and European waters and the second record (after one from Brazil) outside its type locality in deep-water off New England in the north-west Atlantic Ocean. The morphology of the Greek specimens is described and illustrated and diagnostic characters of the species are discussed. The origin of these specimens in the coastal waters of Greece is uncertain and the species is considered as cryptogenic in the Mediterranean Sea. An identification key to Dipolydora species with bristle-topped falcate spines in chaetiger 5 known from the Mediterranean Sea and European waters is provided.

First record of Dipolydora blakei (Annelida: Spionidae) from Europe: Greece, Mediterranean Sea - V. I. RADASHEVSKY; N. SIMBOURA (Mediterranean Marine Science, 2013)

Flabelliderma cinari (Polychaeta: Flabelligeridae), a new species from the Eastern Mediterranean - S.U. KARHAN; N. SIMBOURA; S.I. SALAZAR-VALLEJO (Mediterranean Marine Science, 2012)
A new species of flabelligerid polychaete, Flabelliderma cinari, is described from the Turkish coast of the Eastern MediterraneanSea. This represents the first occurrence of the genus Flabelliderma in the Mediterranean. Flabelliderma cinari sp. nov. isclosely allied to F. claparedei in having dorsal tubercles of two different sizes; however, these species differ in the relative shapeand number of dorsal tubercles, the number of capillaries per fascicle in the notopodia and the shape of the curved distal articlesin the neuropodial hooks.

Flabelliderma cinari (Polychaeta: Flabelligeridae), a new species from the Eastern Mediterranean - S.U. KARHAN; N. SIMBOURA; S.I. SALAZAR-VALLEJO (Mediterranean Marine Science, 2012)

Indicators for the Sea-floor Integrity of the Hellenic Seas under the European Marine Strategy Framework Directive: establishing the thresholds and standards for Good Environmental Status - N. SIMBOURA; A. ZENETOS; M.A. PANCUCCI-PAPADOPOULOU; S. REIZOPOULOU; N. STREFTARIS (Mediterranean Marine Science, 2012)
A data set of 625 samples of benthic macroinvertebrates collected from the Hellenic Seas (Ionian and Aegean) was used to establish thresholds and reference standards for two of the indicators addressing the descriptors of Sea-floor Integrity under the Marine Strategy Framework Directive (MSFD): species diversity and richness and the ratio of sensitive species to tolerant species. The dataset was categorised according to the baseline ecological status assessment of the respective water bodies under the Water Framework Directive (WFD). Species diversity and richness were characterised using the Shannon diversity and species richness indices, respectively, and were analysed for three pre-defined substrate types, three depth zones and three sample-size categories, and the significant categories were statistically validated. Good Environmental Status (GEnS) threshold and reference values were established for the valid combinations of categories denoted as ‘ecotypes’ through the use of a boxplot and an analysis of variance. The limitations and specifications for an overall GEnS assessment using the above indices are highlighted based on the WFD experience. For the ratio of sensitive species to tolerant species, the BENTIX index classification scale is proposed for GEnS assessment, and an integrated approach to the assessment of diversity and species richness is suggested. Finally, the regionality of the tested indices in relation to the two Mediterranean sub-regions, including the Hellenic area, was tested.

An overlooked alien species present on the coasts of Greece (Eastern Mediterranean): the polychaete Polycirrus twisti Potts (Polychaeta: Terebellidae) - N. SIMBOURA (Mediterranean Marine Science, 2011)
The Terebellidae polychaete Polycirrus twisti Potts, 1928 had been confused in several previous records the Eastern Mediterranean with the co-generic species Polycirrus plumosusWollebaeck, 1912, because of incomplete specimens or unclear descriptions; therefore its presence in Greek seas had been overlooked. Specimens of Polycirrus twisti were currently identified from the Korinthiakos Gulf (Greece, Eastern Mediterranean), while older records from the Hellenic marine area, erroneously assigned toPolycirrus plumosus and recorded since 1983 (Rhodos island, Dodekanesse) were emended. Polycirrus twisti is an alien species, most likely introduced to the Mediterranean from the Suez Canal, while it was recently reported from the Southern coasts of Turkey (Levantine Sea). Its identification and report in Greek Seas increases the number of alien polychaete species in this area to 37 and offers a further evidence and link of its introduction and dispersion dynamics from the Suez Canal to the Levantine and Aegean Sea. The presence of the previously reported species Polycirrus plumosus in the Mediterranean Sea is therefore strongly questionable.

Four new alien species on the coasts of Greece (Eastern Mediterranean) - N. SIMBOURA; G. KURT SAHIN; A. PANAGOULIA; N. KATSIARAS (Mediterranean Marine Science, 2010)
This study reports four alien polychaete species new to the marine fauna of Greece. These species are -Pseudopolydora paucibranchiata (family Spionidae),Paraprionospio coora (family Spionidae), Marphysa disjuncta (family Eunicidae), and Chaetozone corona(family Cirratulidae). Another species of Chaetozone, though not an alien one, Chaetozone gibber is reported here from Greek waters. All of them have been currently reported from the coasts of Turkey (Aegean or Levantine Seas). Pseudopolydorapaucibranchiata and Marphysa disjuncta, probably introduced to the region through ballast waters, seem to have been well established in the Mediterranean Sea. Chaetozone corona and Paraprionospio coorawere considered to be cryptogenic. Pseudolydora paucibranchiata was found in great densities in a very disturbed site, confirming the opportunistic character of this species. Chaetozone corona and Chaetozonegibber showed a wider distribution pattern, though their abundance increased in disturbed sites.Marphysa disjuncta was found in disturbed as well as in undisturbed sites along the coasts of Greece.Paraprionospio coora shows a distribution pattern indicating an opportunistic character. These new findings increase the number of polychaete species from the Hellenic Seas to 777 species.

First occurrence of the invasive alien species Polydora cornuta Bosc, 1802 (Polychaeta: Spionidae) on the coast of Greece (Elefsis Bay; Aegean Sea) - N. SIMBOURA; K. SIGALA; E. VOUTSINAS; E. KALKAN (Mediterranean Marine Science, 2008)
The present study reports on the occurrence of two specimens of the alien species Polydora cornutaBosc, 1802, in Elefsis Bay, the Saronikos Gulf (Aegean Sea, eastern Mediterranean). This is the firstrecord of this invasive alien species on the coast of Greece and the second report in the eastern MediterraneanSea after its first finding in Izmir Bay (on the Turkish Aegean coast). This finding enhances its distributionalpattern within the Mediterranean

On the Occurrence and Established Populations of the Alien Polychaete Polydora cornuta Bosc, 1802 (Polychaeta: Spionidae) in the Sea of Marmara and the Bosphorus Strait (Turkey) - S.U. KARHAN; E. KALKAN; N. SIMBOURA; E. MUTLU; M. BEKOLET (Mediterranean Marine Science, 2008)
The present paper reports the first occurrence of Polydora cornuta in the Bosphorus Strait and its finding in a new locality in the Sea of Marmara, providing a link with its Aegean and Black Sea populations. The probable vector for the introduction of P. cornuta into the Sea of Marmara is shipping through the Dardanelles Strait. Both soft and hard-bottom populations were examined and the importance and prevalence of this species within the native macrozoobenthic communities were elucidated. Its abundance ranged between 40 and 3390 ind.m-2 (mean:1320 ±1199.45 SD) and its percent contribution to the total faunal populations ranged between 3.31 and 75.56 (mean:27.79 ±25.00 SD) in the Sea of Marmara softbottom community. During the sampling period, P. cornuta contributed little to the total faunal abundance of the hard-bottom communities in the Bosphorus Strait. Its mean abundance in the hard substrate ranged between 8.33 and 1000 ind.m-2 (mean:117.36 ±279.73 SD) and its percent contribution to the total faunal populations ranged between 0.02 and 21.86 (mean:2.07 ±6.25 SD).The role of this invasive species in the soft-bottom macrobenthic community at an organically enriched site examined in the Sea of Marmara is highlighted, and a comparison with Aegean Sea populations of the species is also included.

First occurrence of the Indo-Pacific polychaete species Glycinde bonhourei Gravier, 1904 in the Hellenic seas (Northern Evvoikos Gulf) - N. SIMBOURA (Mediterranean Marine Science, 2008)
A specimen of Glycinde bonhourei Gravier, 1904, an Indo-Pacific species, was found at a station near the metalliferous waste disposal in the Northern Evvoikos Gulf (Aegean Sea, eastern Mediterranean). This is the second report of this species in the Mediterranean Sea after its first finding in the Levantine basin (Israel and Egypt). This paper provides new information on its distributional range in the Mediterranean Sea.

Application of the bentix index in assessing ecological quality of hard substrata: a case study from the Bosphorus Strait, Turkey - E. KALKAN; S.U. KARHAN; E. MUTLU; N. SIMBOURA; M. BEKOLET (Mediterranean Marine Science, 2007)
In this paper, a biotic index (Bentix) has been used for the assessment of ecological quality status of shallow water hard substrate benthic ecosystems affected by coastal sewage discharges in the Bosphorus Strait. A significant difference was observed between the control and the discharge stations with regard to Bentix values (Mann-Whitney U Test, p=0.002) and ecological quality status of the discharge stations was worse than that of controls. The index values revealed that sewage discharges caused serious disturbance in macrozoobenthic communities in the area investigated. Although so far it has been used for soft bottom communities, Bentix (with some species scoring modifications) also appeared to work successfully in hard substrates, at least for the present study.

Increasing Polychaete diversity as a consequence of increasing research effort in Greek waters: new records and exotic species - N. SIMBOURA; A. ZENETOS (Mediterranean Marine Science, 2005)
The increasing diversity of the Greek Polychaete fauna over the last seven decades, as illustrated graphically, shows an increasing trend which is proportionately related to the research effort exerted. Ongoing research activities mainly in the depths of the N. Aegean Sea, as a result of which 13 new records have been added to the Greek Polychaete fauna, confirming the above statement. The new species records are presented along with their geographical distribution and habitat. According to the latest checklist of the Greek Polychaeta, 753 species of Polychaetes have been recorded in Greek waters. Finally, it should be noted that 6 Lessepsian migrants and 16 species have been recorded in the Mediterranean for the first time. Their distribution within Greece and worldwide is given and their presence in Greek waters is discussed.

Benthic indicators to use in Ecological Quality classification of Mediterranean soft bottom marine ecosystems, including a new Biotic Index - N. SIMBOURA; A. ZENETOS (Mediterranean Marine Science, 2002)
A general scheme for approaching the objective of Ecological Quality Status (EcoQ) classification of zoobenthic marine ecosystems is presented. A system based on soft bottom benthic indicator species and related habitat types is suggested to be used for testing the typological definition of a given water body in the Mediterranean. Benthic indices including the Shannon-Wiener diversity index and the species richness are re-evaluated for use in classification. Ranges of values and of ecological quality categories are given for the diversity and species richness in different habitat types. A new biotic index (BENTIX) is proposed based on the relative percentages of three ecological groups of species grouped according to their sensitivity or tolerance to disturbance factors and weighted proportionately to obtain a formula rendering a five step numerical scale of ecological quality classification. Its advantage against former biotic indices lies in the fact that it reduces the number of the ecological groups involved which makes it simpler and easier in its use. The Bentix index proposed is tested and validated with data from Greek and western Mediterranean ecosystems and examples are presented. Indicator species associated with specific habitat types and pollution indicator species, scored according to their degree of tolerance to pollution, are listed in a table. The Bentix index is compared and evaluated against the indices of diversity and species richness for use in classification. The advantages of the BENTIX index as a classification tool for ECoQ include independence from habitat type, sample size and taxonomic effort, high discriminative power and simplicity in its use which make it a robust, simple and effective tool for application in the Mediterranean Sea.

Coastal benthic diversity in the Black and Aegean Seas - A. ZENETOS; N.K. REVKOV; T. KONSULOVA; N. SERGEEVA; N. SIMBOURA; V.R. TODOROVA; V.E. ZAIKA (Mediterranean Marine Science, 2000)
Quantitative data pertaining to the composition of macrobenthic communities of soft bottoms along the coastal zones of the Black and Aegean Seas are reviewed. The study area includes one site in the Russian coastal zone, four sites in Ukraine (at depths 3-125 m), four sites in Bulgaria (at depths 12-83 m), and four sites in Greece (at depths 9-90 m). The species variety, population density and community diversity are compared between Seas, among regions and among stations. The fluctuation of these parameters in connection to anthropogenic impact (ranging from open undisturbed sites to those receiving heavy organic and chemical effluent) are discussed. The low species number of benthic fauna in the Black Sea, as opposed to the richness of the Aegean Sea (three times higher) a ratio well established for other marine groups, is not reflected in the overall abundance. Thus, the average population density of benthic organisms may reach 12352 ind per m2 in the Black Sea (Cocketrice sandy bank) while in the Aegean it did not exceed 4,000 ind per m2 (Saronikos Gulf). Community diversity was always lower in the Black Sea than similar sites in the Aegean Sea. Within the various regions examined, the protected areas exhibited the most complex community structure.